Bank Runs, Fragility, and Credit Easing - Amador, Manuel; Bianchi, Javier (American Economic Review, 2024)
We present a tractable dynamic general equilibrium model of self-fulfilling bank runs, where banks trade capital in competitive and liquid markets but remain vulnerable to runs due to a loss of creditor confidence. We characterize how the vulnerability of an individual bank depends on its leverage position and the economy-wide asset prices. We study the effect of credit easing policies, in the form of asset purchases. When a banking crisis is generated by runs, credit easing can reduce the number of defaulting banks and enhance welfare. When the crisis is driven by fundamentals, credit easing may have adverse consequences. (JEL E32, E44, E58, G01, G21, G28, G33)